International variations in clinical practice guidelines for palliative sedation: a systematic review. Issue 3 (20th April 2017) - Abarshi, Ebun; Rietjens, Judith; Robijn, Lenzo; Caraceni, Augusto; Payne, Sheila; Deliens, Luc; Van den Block, Lieve
Abstract : Objectives: Palliative sedation is a highly debated medical practice, particularly regarding its proper use in end-of-life care. Worldwide, guidelines are used to standardise care and regulate this practice. In this review, we identify and compare national/regional clinical practice guidelines on palliative sedation against the European Association for Palliative Care (EAPC) palliative sedation Framework and assess the developmental quality of these guidelines using the Appraisal Guideline Research and Evaluation (AGREE II) instrument. Methods: Using the PRISMA criteria, we searched multiple databases (PubMed, CancerLit, CINAHL, Cochrane Library, NHS Evidence and Google Scholar) for relevant guidelines, and selected those written in English, Dutch and Italian; published between January 2000 and March 2016. Results: Of 264 hits, 13 guidelines—Belgium, Canada (3), Ireland, Italy, Japan, the Netherlands, Norway, Spain, Europe, and USA (2) were selected. 8 contained at least 9/10 recommendations published in the EAPC Framework; 9 recommended 'pre-emptive discussion of the potential role of sedation in end-of-life care'; 9 recommended 'nutrition/hydration while performing sedation' and 8 acknowledged the need to 'care for the medical team'. There were striking differences in terminologies used and in life expectancy preceding the practice. Selected guidelines were conceptually similar, comparing closely to the EAPC Framework recommendations, albeit with notable variations. Conclusions: Based on AGREE II, 3 guidelines achieved top scores and could therefore be recommended for use in this context. Also, domains 'scope and purpose' and 'editorial independence' ranked highest and lowest, respectively—underscoring the importance of good reportage at the developmental stage.